2015
DOI: 10.3923/jfas.2016.56.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Mustard (Brassica nigra) on the Interaction between Immune and Biotransformation Systems of Nile Tilapia (Oreochromis niloticus) Exposed to Benzo-a-Pyrene

Abstract: Aquatic pollutants are responsible form any alterations in fish health. Our study was designed to examine the efficacy of dietary supplement of black mustard seed, Brassica nigra (30% crude and 1% alcoholic extract) on enhancement the immunity and detoxification response of Nile tilapia, Oreochromis niloticus after exposed to a hydrocarbon pollutant; Benzo-a-Pyrene (BaP). Fish were divided into 3 groups before being fed for 28 days with crude black mustard seeds,1% alcoholic extract and un-supplemented commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Apines-Amar et al ( 2012) demonstrated that feeding grouper, Epinephelus fuscoguttatus, on onions and ginger-based diets enhanced the innate immune responses and protected fish against experimental infection with Vibrio harveyi. Similar enhancement of nonspecific immune responses was noticed in tilapia fed numerous medicinal herbs such as Brassica nigra (Abbas et al 2016), Moringa oleifera , curcumin (Elgendy et al 2016), fenugreek (Abbas et al, 2019a, b), garlic (Alam et al 2019), and Nigella sativa (Elkamel and Mosaad 2012). Protease, antiprotease, and peroxidase are essential antibacterial components in fish immunedefense mechanisms that play critical roles in protection against invading pathogens .…”
Section: Discussionmentioning
confidence: 54%
“…Apines-Amar et al ( 2012) demonstrated that feeding grouper, Epinephelus fuscoguttatus, on onions and ginger-based diets enhanced the innate immune responses and protected fish against experimental infection with Vibrio harveyi. Similar enhancement of nonspecific immune responses was noticed in tilapia fed numerous medicinal herbs such as Brassica nigra (Abbas et al 2016), Moringa oleifera , curcumin (Elgendy et al 2016), fenugreek (Abbas et al, 2019a, b), garlic (Alam et al 2019), and Nigella sativa (Elkamel and Mosaad 2012). Protease, antiprotease, and peroxidase are essential antibacterial components in fish immunedefense mechanisms that play critical roles in protection against invading pathogens .…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, feeding O . niloticus on diets with 1% Brassica nigra extract stimulated fish immunity with a significant increase ( p < 0.05) in lysozyme activity (Abbas et al, 2016). Lysozyme has long been considered one of the first fish defence lines (Yin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…oleifera ; meanwhile, serum antiprotease and peroxidase levels did not show significant changes. Additionally, enhancement of antiproteases was noticed in fish fed dietary supplementation either with Brassica nigra seeds or leek, Allium ampeloprasum L. (Abbas & Awad, 2016; Abbas et al, 2016). It was well established that antiproteases possess potent anti‐inflammatory and bactericidal properties against bacterial invasion (Esteban, 2012; Jurado et al, 2015).…”
Section: Discussionmentioning
confidence: 99%